Parameters Used for Evaluation of the Response to Treatment with Recombinant Human Growth Hormone in Paediatric and Adult Populations in Poland: Review - Agata Kotkowiak; Mikołaj Łabuda; Agnieszka Szema; Jakub Sikora; Karolina Knychalska; Klaudia Królikowska; Aleksandra Słojewska; Teresa Sowińska; Oliwia Mentel; Adrianna Bogucka (Journal of Education, Health and Sport)
Introduction and purpose